School Principals and Supervisory Competence in Improving Instructional Quality: Perspective Literature Review - Dethia HS; Mutoharoh Mutoharoh; Umalihayati; Syadeli Hanafi; Minhatul Maarif (Southeast Asian Journal of Science and Technology, 2025)
Improving the quality of learning is strongly influenced by the supervisory competence of school principals as instructional leaders. Academic supervision serves to support teachers in developing effective instructional practices oriented toward improving student learning outcomes. This article employs a systematic literature review method to analyze the contribution of principals’ supervisory competence to enhancing instructional quality. The findings indicate that supervisory competence encompasses planning, implementation, evaluation, professional development, and reflection. These five dimensions have been empirically shown to significantly influence instructional quality and teacher professionalism. This article underscores the importance of strengthening principals’ supervisory competence through continuous training and sustainable professional development programs.